To my beloveds : letters on faith, race, loss, and radical hope - Bailey, Jennifer (Reverend) (Chalice Press, 2021)
"How do we heal our grief and loss to become the leaders the world needs today? In this unique collection love letters to her fellow activists and faith leaders, Jennifer Bailey offers comfort, wisdom, encouragement, support, and hope for young activists and emerging faith leaders aspiring to build a better world amidst its violence, trauma, and loss--and who may wonder if they're up to the task or unsure if they'll ever see the change they seek. Considering three central questions--what is dying, what wants to emerge, and what is already blooming beautifully--Bailey's poignant letters inspire us to imagine how our grief and despair can be composted into new life filled with courage, hope, and purpose for our shared future."--Publisher's website.